2018
DOI: 10.37570/bgsd-2018-66-06
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy and geothermal assessment of Mesozoic sandstone reservoirs in the Øresund Basin – exemplified by well data and seismic profiles

Abstract: The Øresund Basin in the transnational area between Sweden and Denmark forms a marginal part of the Danish Basin. The structural outline and stratigraphy of the Mesozoic succession is described, and a novel interpretation and description of the subsurface geology and geothermal potential in the North Sjælland Half-graben is presented. The subsurface bedrock in the basin includes several Mesozoic intervals with potential geothermal sandstone reservoirs. Parts of the succession fulfill specific geological requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Rosberg and Erlström (2019) reported that the temperature gradient in the sedimentary succession in DGE-1 was much lower than expected and that is an explanation of the lower bottomhole temperature in DGE-1. In FFC-1, the temperature gradient in the sedimentary succession was like gradients, between 28-32°C/km, observed in other wells located in the sedimentary succession in southwest Skåne (Erlström et al 2018).…”
Section: Thermal Gradientmentioning
confidence: 54%
“…Rosberg and Erlström (2019) reported that the temperature gradient in the sedimentary succession in DGE-1 was much lower than expected and that is an explanation of the lower bottomhole temperature in DGE-1. In FFC-1, the temperature gradient in the sedimentary succession was like gradients, between 28-32°C/km, observed in other wells located in the sedimentary succession in southwest Skåne (Erlström et al 2018).…”
Section: Thermal Gradientmentioning
confidence: 54%
“…These structural differences exert a decisive influence on the geothermal prospectivity of the Danish subsurface, as they essentially determine the distribution, thicknesses, facies types and burial depths of the potential reservoirs (e.g. Nielsen 2003;Nielsen et al 2004;Erlström et al, 2018).…”
Section: Study Area and Geological Settingmentioning
confidence: 99%